Contribution to the genus Pararrhynchium de Saussure (Hymenoptera: Vespidae: Eumeninae), with description of two new species from Vietnam - Nguyen, Lien Thi Phuong; Tran, Ngat Thi; Bui, Dien Trong; Ljubomirov, Toshko (Zootaxa, 2021)
Two new species of the genus Pararrhynchium de Saussure are described as new to science: P. simsanum Nguyen and Tran, sp. nov. from Bat Xat, Lao Cai province, and P. sparsum Nguyen and Ljubomirov, sp. nov. from Ham Yen, Tuyen Quang province. An updated key to all known species of the genus is also presented.